Lets rewrite the equation as below:
"\\left(xy^2-x^2\\right)dx+\\left(3x^2y^2+x^2y-2x^3+y^2\\right)dy=0\\\\[0.3cm]\np(x,y)dx+q(x,y)dy=0\\\\[0.3cm]\n\\left\\{\\begin{array}{l}\np(x,y)=xy^2-x^2\\\\[0.3cm]\nq(x,y)=3x^2y^2+x^2y-2x^3+y^2\n\\end{array}\\right."
The equation is called exact differential equation if it satisfied:
"\\frac{\\partial p(x,y)}{\\partial y}=\\frac{\\partial q(x,y)}{\\partial y}"
In our case,
"\\left\\{\\begin{array}{l}\n\\displaystyle\\frac{\\partial p}{\\partial y}=2xy\\\\[0.3cm]\n\\displaystyle\\frac{\\partial q}{\\partial x}=6xy^2+2xy-6x^2\n\\end{array}\\right.\\longrightarrow\\\\[0.3cm]\n\\frac{\\partial p}{\\partial y}\\neq\\frac{\\partial q}{\\partial x}"
Since the relation is not equal, this differential equation is not exact.
Next step is find a function "u(x,y)" which will make equation
"u(x,y)(p(x,y)dx+q(x,y)dy)=0" become exact differential equation.
"u(x,y)" is called integrating factor, and will be much easier to find if it is only "x" function or only "y" function.
"u(x,y)" is only x function if
"u(x,y)\\equiv u(x)=\\frac{\\displaystyle\\frac{\\partial p}{\\partial y}-\\displaystyle\\frac{\\partial q}{\\partial x}}{q(x,y)}"
only have "x" variable, and it is only "y" function if
"u(x,y)\\equiv u(y)=\\frac{\\displaystyle\\frac{\\partial q}{\\partial x}-\\displaystyle\\frac{\\partial p}{\\partial y}}{p(x,y)}"
only have "y" variable.
In our case,
"\\frac{\\displaystyle\\frac{\\partial p}{\\partial y}-\\displaystyle\\frac{\\partial q}{\\partial x}}{q(x,y)}=\\frac{2xy-\\left(6xy^2+2xy-6x^2\\right)}{3x^2y^2+x^2y-2x^3+y^2}\\\\[0.3cm]\n\\frac{\\displaystyle\\frac{\\partial p}{\\partial y}-\\displaystyle\\frac{\\partial q}{\\partial x}}{q(x,y)}=\\frac{6x\\left(x-y^2\\right)}{3x^2y^2+x^2y-2x^3+y^2}\\\\[0.3cm]"
contain both "x" and "y" .
"\\frac{\\displaystyle\\frac{\\partial q}{\\partial x}-\\displaystyle\\frac{\\partial p}{\\partial y}}{p(x,y)}=\\frac{\\left(6xy^2+2xy-6x^2\\right)-2xy}{xy^2-x^2}\\\\[0.3cm]\n\\frac{\\displaystyle\\frac{\\partial q}{\\partial x}-\\displaystyle\\frac{\\partial p}{\\partial y}}{p(x,y)}=\\frac{6x\\left(y^2-x\\right)}{x(y^2-x)}=6\\\\[0.3cm]"contain only "y" variable.
So "u(x,y)" is only "y" function. In this case:
"u(y)=e^{\\int 6dy}=e^{6y}"
Back to our initial equation:
"u(y)(p(x,y)dx+q(x,y)dy)=0\\\\[0.3cm]\ne^{6y}\\left(xy^2-x^2\\right)dx+e^{6y}\\left(3x^2y^2+x^2y-2x^3+y^2\\right)dy=0"
Now find a function "f(x,y)" that satisfied:
"\\left\\{\\begin{array}{l}\n\\displaystyle\\frac{\\partial f}{\\partial x}=e^{6y}\\left(xy^2-x^2\\right)\\\\[0.3cm]\n\\displaystyle\\frac{\\partial f}{\\partial y}=e^{6y}\\left(3x^2y^2+x^2y-2x^3+y^2\\right)\n\\end{array}\\right.\\\\[0.3cm]\n\\frac{\\partial f}{\\partial x}=e^{6y}\\left(xy^2-x^2\\right)\\longrightarrow\\\\[0.3cm]\nf(x,y)=\\int\\left(e^{6y}\\left(xy^2-x^2\\right)\\right)dx+g(y)\\longrightarrow\\\\[0.3cm]\n\\boxed{f(x,y)=e^{6y}\\left(\\frac{x^2y^2}{2}-\\frac{x^3}{3}\\right)+g(y)}\\\\[0.3cm]\n\\frac{\\partial f}{\\partial y}=\\frac{\\partial}{\\partial y}\\left(e^{6y}\\left(\\frac{x^2y^2}{2}-\\frac{x^3}{3}\\right)+g(y)\\right)=\\\\[0.3cm]\n=6\\cdot e^{6y}\\left(\\frac{x^2y^2}{2}-\\frac{x^3}{3}\\right)+e^{6y}\\left(x^2y\\right)+\\frac{dg}{dy}=\\\\[0.3cm]\n=e^{6y}\\left(3x^2y^2-2x^3+x^2y\\right)+\\frac{dg}{dy}" Then,
"e^{6y}\\left(3x^2y^2-2x^3+x^2y\\right)+\\frac{dg}{dy}=e^{6y}\\left(3x^2y^2+x^2y-2x^3+y^2\\right)\\\\[0.3cm]\n\\frac{dg}{dy}=e^{6y}\\cdot y^2\\longrightarrow g(y)=\\int\\left(e^{6y}y^2\\right)dy\\\\[0.3cm]\n\\left(\\text{integration by parts}\\right) : \\\\[0.3cm]\ng(y)=\\int\\left(e^{6y}y^2\\right)dy=\\frac{y^2e^{6y}}{6}-\\int\\frac{2e^{6y}}{6}dy=\\\\[0.3cm]\n=\\frac{y^2e^{6y}}{6}-\\frac{1}{3}\\cdot\\left(\\frac{ye^{6y}}{6}-\\int\\frac{e^{6y}}{6}\\right)=\\\\[0.3cm]\n=\\frac{y^2e^{6y}}{6}-\\frac{ye^{6y}}{18}-\\frac{e^{6y}}{108}\\equiv\\frac{e^{6y}\\left(18y^2-6y+1\\right)}{108}"
Conclusion,
"\\boxed{f(x,y)=f(x,y)=e^{6y}\\left(\\frac{x^2y^2}{2}-\\frac{x^3}{3}\\right)+\\frac{e^{6y}\\left(18y^2-6y+1\\right)}{108}}"
And finally our equation can be rewriten as:
"\\frac{\\partial f(x,y)}{\\partial x}\\cdot dx+\\frac{\\partial f(x,y)}{\\partial y}\\cdot dy=df(x,y)=0\\\\[0.3cm]\nf(x,y)=C\\\\[0.3cm]\n\\boxed{e^{6y}\\left(\\frac{x^2y^2}{2}-\\frac{x^3}{3}\\right)+\\frac{e^{6y}\\left(18y^2-6y+1\\right)}{108}=C}"
ANSWER
General solution
"e^{6y}\\left(\\frac{x^2y^2}{2}-\\frac{x^3}{3}+\\frac{18y^2-6y+1}{108}\\right)=C"
Comments
Leave a comment